The Dilemma of Public Hearings in Land Expropriation in China Based on Farmers’ Satisfaction - Jiang, Lin; Sun, Li; Fu, Zhenyi; Qi, Rui; Tang, Tao; Lin, Qiaowen (Frontiers in Environmental Science, 2022)
Although public hearings have been introduced into Chinese land expropriation as an important democratic supervision and conflict resolution mechanism for more than 15 years, there is a dearth of research into its qualities. Taking the farmers’ satisfaction with the public hearings as the critical quality indicator, this paper analyzes the dilemma of this special institution in Chinese land expropriation. Process tracing is employed to analyze the design defect of the public hearing institution. Farmers’ satisfactions with the public hearings are measured by a questionnaire, and the factors are examined by a Structural Equation Model based on the theories of expectancy disconfirmation and procedural fairness. It’s concluded that the distorted procedure and the inconsiderate arrangement affect farmers’ perceived procedural fairness and decrease their satisfaction with hearings. In order to solve the dilemma of public participation in land expropriation, the relevant authorities should start from the source of affecting farmers' satisfaction.